2013
DOI: 10.1017/s0266467413000497
|View full text |Cite
|
Sign up to set email alerts
|

Soil modification by termites in a sandy-soil vegetation in the Brazilian Atlantic rain forest

Abstract: Abstract:Termites play a critical role in the regulation of soil processes, for example, water retention, nutrient cycling, and the formation and maintenance of soil structure. There is a consensus that mound-building termites modify physical and chemical soil properties in clay soils, but there is limited investigation into their influence for sandy soils in the Brazilian Atlantic rain forest. We tested the hypotheses that the termitosphere effectively improves properties of sandy soil, and that the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…The results of this study corroborate those of Peres Filho et al (1990) and Sarcinelli et al (2013), who found higher clay contents in mounds than in soils at different sampling distances. A higher clay content in mounds was also reported by Oliveira et al (2012), but not for the other fractions.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study corroborate those of Peres Filho et al (1990) and Sarcinelli et al (2013), who found higher clay contents in mounds than in soils at different sampling distances. A higher clay content in mounds was also reported by Oliveira et al (2012), but not for the other fractions.…”
Section: Resultssupporting
confidence: 92%
“…Subsequently, the soil around the mounds was sampled. Single samples were collected from around each nest (layers 0.00-0.05 and 0.05-0.10 m), at distances of 0.50 and 1.50 m from the mound base, the same as used in other studies (Kaschuk et al, 2006;Sarcinelli et al, 2009;Joseph et al, 2013;Sarcinelli et al, 2013). Per mound, a total of four samples were retrieved from the surrounding soil (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Termites produce enzyme‐ and microbial‐rich faeces and hence contribute to the soil microbial pool and to nutrient redistribution (Jouquet et al ., ). The nutrients in ingested matter that are not used by the termites are deposited within the mound, with these mounds consequently becoming nutrient rich relative to the surrounding area (Brauman, ; Sarcinelli et al ., ). As a result, these fertile mounds are characterised by vegetation that differs from that found in the rest of the habitat (Muvengwi et al ., ).…”
Section: The Ecological Importance Of Termitesmentioning
confidence: 97%
“…Moreover, the Collembola (microphages) also influenced the decomposition of plant residues by fragmenting them and playing an important role in soil microstructure formation, creating a favorable balance between bacteria and fungi, producing enzymes (Nunes, 2003). Termites also have a key function in soil structure formation in Latosols (Schaefer, 2001;Sarcinelli et al, 2013).…”
Section: Discussionmentioning
confidence: 99%